Renegotiating societal-military relations in Pakistan: the case of the Pashtun Tahafuz Movement. Issue 2 (17th February 2021) - Aslam, Wali; Neads, Alex
ABSTRACT: This article examines the Pakistani military's changing response to the Pashtun Tahafuz Movement (PTM), to better understand pathways to military accountability and democratic change. An apolitical, non-violent civil-society movement, the PTM challenged the military's domestic-security practices for over a year, eliciting uncharacteristic concessions despite the apparent motive, opportunity and precedent for repression. Curiously, though, the role of civil society in renegotiating military behaviour has been overlooked in mainstream civil–military relations, which focuses on coup propensity at one extreme and harmonious democratic configurations at the other. Using first-hand interviews with PTM activists, security officials, commentators and politicians, this study argues that the PTM's unique appeal to societal and constitutional legitimacy constrained military responses, creating an opportunity to contest military behaviour publicly in a fashion impossible for conventional political elites. Although the military eventually resorted to force, this was itself facilitated by attacks on the underlying parameters of the PTM's societal legitimacy, underscoring the importance of societal -military relations in the space between civilian control and coup d'état.